PENGGUNAAN PENDEKATAN SUKU KATA GUNA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN 09 TANJUNG LAY - Aguarti, Titania; Wibowo, Deki; Rudiansyah, Eko (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
The research is based on the low reading ability of first grade elementary school ssudents. The purpose of the study was to determine the improvement of early reading skills using a syllable approach. The research method uses classroom action research. The research subjects were first grade elementary school students. The object of the study was to improve the ability to read beginning through the use of a syllable approach. The research instrument used observation sheets, learning implementation sheets. Data collection techniques using tests, observations, documentation. The results of the study were the ability to read at the beginning of the first cycle of students completed as many as 7 people with a percentage of 33.33% and students who did not complete as many as 14 people with a percentage of 66.66%. While the average value of the implementation of learning in the first cycle obtained a value of 71.59%. In the second cycle, the initial reading ability that met the criteria for completeness was 17 students with a percentage of 80.95%, while students who did not meet the criteria for completeness were 4 people with a percentage of 19.04. While the average value of the implementation of learning in the second cycle obtained a value of 91.30%. There was an increase in students' initial reading ability from cycle I to cycle II of 47.62%. The conclusion